2016
DOI: 10.1039/c6an00236f
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and selective isolation of rare tumor cells using a microfluidic chip with wavy-herringbone micro-patterned surfaces

Abstract: Circulating tumor cells (CTCs) in peripheral blood have been recognized as a general biomarker for diagnosing cancer and providing guidance for personalized treatments. Yet due to their rarity, the challenge for their clinical utility lies in the efficient isolation while avoiding the capture of other non-targeted white blood cells (WBCs). In this paper, a wavy-herringbone (HB) microfluidic chip coated with antibody directly against epithelial cell adhesion molecule (anti-EpCAM) was developed for highly effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…Various studies have shown the ability to isolate and capture CTCs in lung cancer patients, using a range of platforms, from antibody based (14,15) to filtration based techniques (4,5), with varying levels of performance and success.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown the ability to isolate and capture CTCs in lung cancer patients, using a range of platforms, from antibody based (14,15) to filtration based techniques (4,5), with varying levels of performance and success.…”
Section: Discussionmentioning
confidence: 99%
“…65 This WBC background could be attributed to low shear stagnate regions of fluid within the crevices of the herringbone grooves. 143,144 The herringbone chip has been used in numerous clinical demonstrations (Table 1) with high median CTC counts, especially for prostate cancer, and clinical sensitivities ranging between 56% – 93%. 28,41,65,75,141,142,145 …”
Section: Microfluidic-based Biological Ctc Selectionmentioning
confidence: 99%
“…Moreover, it has been observed that CTM containing up to 20 cells may adopt reversible single-file chain-like geometries which helps them traverse through 5-10 µm constrictions, a striking observation which may have implications in the usage of filtration based devices for CTM enrichment (Au et al, 2016). (Wang et al, 2016). Marker dependent isolation of CTM, whether by macroscale approaches or microfluidic platforms, faces another challenge.…”
Section: Technical Challenges In Devising Ctm Enrichment/isolation Mementioning
confidence: 99%